2017
DOI: 10.1001/jama.2017.15686
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Burden of Health Care Costs on US Families

Abstract: Affording health care has become a pressing national concern. According to a 2016 Gallup survey, 27% of individuals in the United States identified affordability as the country's "most urgent health problem." 1 The level of concern is both severe and new. In the late 1990s, HIV/AIDS was the top health concern. In 2008, the leading health concern was accessing medical services. Today, 57% of individuals report that they worry "a great deal" about "theavailabilityandaffordabilityofhealthcare." 1 Morethan 60% ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 3 publications
(5 reference statements)
0
35
0
Order By: Relevance
“…Health care costs have been growing rapidly in recent decades, and currently represent approximately one third of the median household income for families in the USA [29]. Health care costs and affordability are therefore considered an urgent problem in the USA [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care costs have been growing rapidly in recent decades, and currently represent approximately one third of the median household income for families in the USA [29]. Health care costs and affordability are therefore considered an urgent problem in the USA [29].…”
Section: Discussionmentioning
confidence: 99%
“…Health care costs have been growing rapidly in recent decades, and currently represent approximately one third of the median household income for families in the USA [29]. Health care costs and affordability are therefore considered an urgent problem in the USA [29]. Increases in health care costs in the USA are unsustainable [29,30], and one of the most realistic short-term strategies to address high prices include indentifying conditions where relatively straightforward interventions can save the most resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family health insurance premiums, as a percentage of median income, have continued to rise and doubled over the past 2 decades. 11 The American Hospital Association's Environmental Scan reports that half of the public is at least somewhat worried they won't be able to afford needed healthcare services. Four in 10 (43%) adults with health insurance say they have difficulty affording their deductible, and roughly a third say they have trouble affording their premiums and other cost sharing.…”
Section: Healthcare Financementioning
confidence: 99%
“…To personalize the actual cost and affordability of health care, Emanuel, Glickman, & Johnson (2017) proposed the development of an "Affordability Index" [2], which relates the average cost of health care to the average household income. The authors themselves indicated that the index is not perfect in determining the affordability of health care services.…”
Section: Literature Reviewmentioning
confidence: 99%